Social Identity and Political Preferences of First-Time Voters in the 2024 Presidential Election - Rahmiaji, Lintang Ratri; Sulistyani, Hapsari Dwiningtyas; Rahardjo, Turnomo (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
Reaching voters in presidential elections frequently involves using identity politics. On the other side, first-time voters might serve as prospective targets for gaining supporters. This study aims to investigate the link between first-time voters' choices for presidential candidates and the social identities (faith, gender, and ethnicity) of presidential candidates. Social Identity Theory is the leading theory that explains the relationship between social identity and political choice preferences. This quantitative survey study looks at the relationship between political candidates' social identities and the preferences of first-time voters in Indonesia in 2023. The study's findings indicate a connection between the presidential and vice-presidential candidates' social identities and the decisions made by first-time voters. For instance, the political choices of first-time voters are directly correlated with their gender, notably whether they will accept or approve of female presidents and vice presidents. The study's findings indicate that first-time voters are open to electing a female president. An interesting finding to highlight is how new voters tend to be open to the choice of president and vice president of other religions. Most first-time voters (respondents) accept presidents and vice presidents from minority religions such as Catholics, Christians, Buddhists, Hindus, Confucians, and local religions.